Review on Computer Aided Detection Systems of Breast Cancer - A.M.Solanke; R.Manjunath; D.V.Jadhav (International Journal of Psychosocial Rehabilitation, 2020)
Breast cancer is life threatening disease for women.According to World Health Organisation breast cancer is second leading cause of death in the world.Many lives can be saved by early detection of breast cancer.Most widely used breast cancer screening technique is mammography. Mammography is used for detection and clinical evaluation of breast cancer. Computer aided detection techniques(CAD) are used to assist doctors and radiologists for analysing mammograms.CAD techniques plays very important role in early detection of breast cancer.In this paper total forty five papers are referred to present overview of signs of breast cancer,screening technique and survey of algorithms for detection of Micro-calcifications,masses and architectural distortion.